On Hilfer-Type Fractional Impulsive Differential Equations - Chanisara Metpattarahiran; Kulandhaivel Karthikeyan; Panjaiyan Karthikeyann; Thanin Sitthiwirattham (International Journal of Differential Equations)
Using the Schauder fixed point theorem, we prove the existence of impulsive fractional differential equations using Hilfer fractional derivative and nearly sectorial operators in this paper. We’ve gone over the two scenarios where the related semigroup is compact and noncompact for this purpose. We also go over an example to back up the main points.